Impact of land conversion on macrofungal diversity in North Selangor Peat Swamp Forest in Malaysia - Rajihan, Siti Noor Shuhada (2017)
Conservation status of macrofungal diversity in the tropical peat swamp forest, particularly in Southeast Asia is still incomplete due to the paucity of information about this taxa. Especially when the peat swamp forest is being degraded and rapidly reduced due to forest fire (El-Nino) and oil palm expansion. North Selangor Peat Swamp Forest (NSPSF) is among the remaining peatlands which are actively threatened by this catastrophe and anthropogenic activities. This study aimed to determine the effects of forest conversion area to oil palm plantation on macrofungal biodiversity. In January 2016, a total of 757 collections of macrofungal sporocarps from 127 genera or known as morphospecies were found in 60 circular units, each 0.79 ha in size. The macrofungal morphospecies and abundance in four different habitats namely logged peat swamp forest, large-scale oil palm plantation, monoculture and polyculture smallholdings were compared using one-way Analysis of Variance (ANOVA) Tukey’s test, while morphospecies composition was examined using non-metric multidimensional scaling (NMDS) ordination. Environmental factors namely air temperature, relative humidity, soil pH, soil moisture and wind speed; as well as canopy closure, canopy cover and substrate availability were analyzed using simple linear regression to investigate their association with macrofungal diversity. The results show that macrofungal diversity of logged peat swamp forest were significantly (P<0.001) higher than macrofungal communities of oil palm based area. Through analysis of similarities (ANOSIM) logged peat swamp forest was found to exhibit variety of macrofungal composition which are not familiar to large-scale plantation, monoculture and polyculture smallholdings (P < 0.001). Macrofungal communities of all habitats were found to show a strong correlation with substrate. Monoculture smallholding was the only habitat showing positive association with two other variables i.e., temperature and soil moisture. The results demonstrated that all habitats support a great value of macrofungal biodiversity. Nevertheless, since the results found that peat swamp forest supports greater macrofungal diversity than oil palm lands, it is important that further expansion of oil palm plantations are to be prohibited on forest land and be shifted to wasted land as an initiative for the land improvement.